A critique of science research in Malaysia - Baharuddin, A.; Hasan, M.A. (1983)
The aim of the paper is to give a general overview of the state of Science research in Malaysia today, i.e. to try to evaluate its successes in terms of the needs of the nation and the problems that it faces. In doing this the authors try to argue for the case of encouraging a greater component of indigenous science to be considered in the research fraternity. Finally some suggestions as to how the above could be implemented are given.